Mechanical design of a standing frame adapted for children with mental deficiency - Laranjeira, Mariana (2018)
The present paper presents the conceptual mechanical design of a Standing Frame for children with mental deficiency. Those children deal with great difficulties in maintaining a correct biped posture, hindering certain system organs to work in its fullness. Thus, the target goal of this project is to provide a correct biped posture to the child with mental deficiency. To achieve this goal there were defined the main goals that the standing frame should fulfil: safety, comfort, adaptability, attractiveness and accessibility. After the definition of certain functions and specifications the final solution comes up. For this solution it was selected metallic materials (structure of the Standing Frame) and polymeric materials (supports). It was also needed to select a lifting system, to lift the child from the seat to the biped position. The best solution found was an hydraulic, linear and single acting actuator. In order to ecologically guide the project it was chosen materials with fabrication and recycling processes that allow the final solution to be the most ecologic as possible.